2014
DOI: 10.1186/s40510-014-0066-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of laser-assisted cosmetic smile lift gingivectomy on postoperative bleeding and pain in fixed orthodontic patients: a controlled clinical trial

Abstract: Background and objectiveDiode lasers are becoming popular in gingival treatment following orthodontic treatments. Despite their merit and clinical implications, postoperative pain and bleeding after surgery with diode lasers are not assessed except in few controversial studies.MethodThis controlled clinical trial was conducted on 30 healthy orthodontic patients aged 17–29 years, needing esthetic-only gingivectomy in the anterior maxilla. The patients were randomly divided into two groups of 15 each: experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 37 publications
1
65
1
3
Order By: Relevance
“…Table 1 shows a summary of clinical trials that were included in this study. Four studies used laser for gingivectomy 10,29,31,32 and 2 studies reported labial frenectomy. 19,32 Lingual frenectomy was investigated by 2 articles.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Table 1 shows a summary of clinical trials that were included in this study. Four studies used laser for gingivectomy 10,29,31,32 and 2 studies reported labial frenectomy. 19,32 Lingual frenectomy was investigated by 2 articles.…”
Section: Resultsmentioning
confidence: 99%
“…However, the types of topical anesthetic drugs are not the same. Junior et al and Aboelsaad and Attia 29 have used benzocaine 20% compared with Seifi et al, To et al 10 and Sobouti et al 31 that have applied tetracaineadrenaline-cocaine also called as TAC 20% (lidocaine 20%, tetracaine 4%, and phenylephrine 2%). Other authors did not mention the type of topical anesthetic that was used.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations